State-organized crime, international law and structural contradictions - Kramer, Ronald C. (Critical criminology, 2016)
Following the trail blazed by Bill Chambliss in his 1988 Presidential Address to the American Society of Criminology, this article engages two interrelated issues concerning the concept of state-organized crime that he pioneered. First, the article develops Chambliss’s argument that criminologists should define state crime as behavior that violates international agreements and principles established in the courts and treaties of international bodies. Second, although Chambliss effectively argued that international law "on the books" provides a framework of substantive concepts and categories that allows criminologists to define certain state actions as a form of crime, "in action" international laws fail to provide legal accountability for states and protection for victims. This article demonstrates, however, that Chambliss’s structural contradictions theory of law can help to explain this paradox.